2003
DOI: 10.1002/ceat.200390023
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Discrete Element Method in Process Engineering

Abstract: This paper provides insight into the application of discrete element modeling in the field of bulk solids handling. This is shown with examples starting with the calibration of a virtual numerical material used in the simulation to mimic the actual material's behavior. Based on the calibration of the material, solid handling problems such as the flow patterns and the stress distribution in silos are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The shear simulations showed that increasing both the particle contact stiffness and static friction coefficient increased the bulk internal friction angle due to the interlocking phenomenon, which also was acknowledged by Cleary (2008) due to the higher number of contacts with neighbouring non‐spherical particles. Härtl and Ooi (2008) and Theuerkauf et al (2003) also observed that the bulk internal friction is related in a non‐linear manner to the particle friction coefficient.…”
Section: Introductionmentioning
confidence: 93%
“…The shear simulations showed that increasing both the particle contact stiffness and static friction coefficient increased the bulk internal friction angle due to the interlocking phenomenon, which also was acknowledged by Cleary (2008) due to the higher number of contacts with neighbouring non‐spherical particles. Härtl and Ooi (2008) and Theuerkauf et al (2003) also observed that the bulk internal friction is related in a non‐linear manner to the particle friction coefficient.…”
Section: Introductionmentioning
confidence: 93%
“…Compared with continuum methods, the advantage of our DEM modeling is that crack propagation and coalescence during the pull‐apart basin development can be directly observed based on fracture mechanical theory with explicit consideration of material separation. The present study uses the two‐dimensional Particle Flow Code (PFC 2D ) (Itasca, ), which is widely used in engineering (e.g., Theuerkauf et al, ), as well as soil and rock mechanics (e.g., Ding et al, ; Groh et al, ; Potyondy & Cundall, ; Sarfarazi et al, ; Stahl & Konietzky, ; Ting et al, ; Wang et al, ). It has also been successfully used to simulate geologic problems (e.g., Chu et al, ; Lee et al, ) and tectonic processes such as the growth and interaction of faults and the formation of related structures (e.g., Imber et al, ; Peacock & Xing, ; Schöpfer et al, , , ).…”
Section: Introductionmentioning
confidence: 99%
“…The elements interact with each other via a force displacement law and can be of arbitrary shape, rectangular blocks and spheres being the most common ones. Applications range from mining and engineering [ Theuerkauf et al , 2003] to seismicity [ Toomey and Bean , 2000] to soil and rock mechanics [ Hart , 2003]. Recently, the DEM has also been used to model tectonic processes such as the formation of shear zones and deformation bands [ Antonellini and Pollard , 1995; Mora and Place , 1998; Morgan and Boettcher , 1999], displacement transfer and linkage of preexisting faults [ Walsh et al , 2001; Imber et al , 2004], and failure in brittle rock on a small scale [ Donzé et al , 1994; Hazzard et al , 2000] and on a large scale [ Saltzer and Pollard , 1992; Burbidge and Braun , 2002; Strayer and Suppe , 2002; Finch et al , 2003, 2004; Strayer et al , 2004; Cardozo et al , 2005; Seyferth and Henk , 2006].…”
Section: Introductionmentioning
confidence: 99%